Payroll clearing of contributions as a source of financing of National Service Learning institute SENA and family welfare icbf by income tax equity for CREE (2014)
The Law 1607 of 2012, established by the Colombian government specifically has two main objectives: on one hand generate more jobs and on the other side to obtain a better distribution of income within the country. Thus, the reform states that instead of financing the SENA, ICBF and the health system with employment taxes, it should based on corporate profits, to be more precise, replaces contributions by companies to these institutions with a tax equity of 8%, this means that companies will reduce your rate of income tax, which in theory would allow generation of additional economic resources to generate more employment units with thus, it generates more income which is going to be distributed among the population, as a natural result would yield further growth of the economy as and as consequence citizens will increase the probability of consumption in goods and services.